China, Kambodscha, Vietnam. Bronzetrommeln aus Südostasien. Die Arbeiten der Jahre 2017 und 2018 - Reinecke, Andreas; Fu, Xia; Bode, Michael (e-Forschungsberichte des DAI, 2018)
The project extends the inventory of all bronze drums in China that were produced from the 5th century BC to the 19th century AD to the regions of Southeast Asia and to the majority of drums that have been brought to Europe in the last 150 years. The aim of the German side is to evaluate the different drum variants of the earliest type Heger I (5th – 1st c. BC) in the South Chinese – Southeast Asian region as far as Indonesia and the Thai-Malay Peninsula on the basis of precise distribution maps for different variants. This first chorological analysis is combined with the documentation of accompanying offerings from graves and metal analyses of drums and contemporary artefacts. In this way, we hope to get closer to the location of casting sites, workshop areas, distribution routes and dating of the early bronze drums in Southeast Asia.